2016
DOI: 10.15344/2456-8007/2016/106
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary and Alternative Medicine Among Patients with Type 2 Diabetes Mellitus in a Newly Developing Country: a Cross- Sectional Study in Qatar

Abstract: Background: Scarce data exists on the utilization of complementary alternative medicine (CAM) among patients with diabetes mellitus (DM) in Qatar. Primary care clinics offer an ideal opportunity to explore the knowledge, attitudes and practice of CAM among patients with type II diabetes. Methods: A total of 226 subjects with type II diabetes were examined in this cross-sectional descriptive study. SPSS v. 19 was used to analyze the data and predictors of CAM use were identified through the utilization of mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…6,12,17,18 The participants of the current study revealed that most important reasons for using CAM was the expectation that CAM will reduce their symptoms, avoid complications besides being safe. Among CAM users only small proportions of the patients (2%) did experience difficulty in controlling their blood-sugar levels inspite of addition of CAM modality to their conventional Anti-diabetic medications.…”
Section: Discussionmentioning
confidence: 83%
“…6,12,17,18 The participants of the current study revealed that most important reasons for using CAM was the expectation that CAM will reduce their symptoms, avoid complications besides being safe. Among CAM users only small proportions of the patients (2%) did experience difficulty in controlling their blood-sugar levels inspite of addition of CAM modality to their conventional Anti-diabetic medications.…”
Section: Discussionmentioning
confidence: 83%
“…In the present study, the difference between age, gender, marital status, educational status, employment status and perceived income status was not significant (Table 1). When the current literature is examined, it has been determined that the study results concerning the use of CAM vary according to the sociodemographic data 11,14,16,19,33,41,43 . The differences in socio-demographic data can be thought to be associated with the effect of cultural and environmental factors in the regions where the studies were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…This form was prepared based on the literature by the researchers and involved a total of 9 questions to determine the state of the patients to use CAM, their reasons of using CAM, CAMs used by them, persons recommending the use of CAM, the outcome expected from the use of CAM, the side effect of the used CAM method, the health status perceived before and after the CAM use, and sharing of the used CAM with the healthcare personnel 13,14,16,18 .…”
Section: Questionnaire For Complementary and Alternative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…There is insufficient evidence to make recommendations regarding the efficacy and safety of complementary or alternative medicine for individuals with diabetes [8]. In certain Eastern and ethnic cultures, CAM treatment plays an integral part in an individual's health belief system, where religious teachings, rituals, and family influences play a major role in an individual's health behavior [9]. Diabetics tend to use herbal remedies to minimize dissatisfaction with conventional therapies, their concerns about possible side effects caused by conventional therapies, and believe that herbal remedies from natural sources are safer and more effective [7].…”
Section: Introductionmentioning
confidence: 99%